Glass free, non-aqueous LTCC tapes of Bi4(SiO4)3 with high solid loading. Issue 8 (August 2015) - Abhilash, Pullanchiyodan; Sebastian, Mailadil Thomas; Surendran, Kuzhichalil Peethambharan
Abstract Glass free Bi4(SiO4)3 ceramic tapes were prepared by non-aqueous solvent based tape casting technique. A higher powder loading above 65 wt.% was achieved in a silicate system through a judicious selection of suitable dispersants and binder. The amount of dispersant was optimized at 1.0 wt.% based on viscosity and sedimentation analysis. The surface morphology and mechanical strength of the green tapes were investigated. The as-prepared green tape of thickness 70 μm has an average surface roughness of 320 nm and a tensile strength of 0.37 MPa. The microwave dielectric properties of the green tape (ɛr = 6.2 and tanδ = 0.0390) and sintered tape (ɛr = 13.3 and tanδ = 0.0007) were measured at 15 GHz by using SPDR technique.